PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KONSERVATISME AKUNTANSI - Vika Fitranita (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2019)
This study aims to analyze the influence of corporate governance mechanisms on accounting conservatism in Real Estate and Property Companies listed on the Indonesia Stock Exchange (IDX) in 2012-2017. In this study, good corporate governance is analyzed as a factor that can encourage the achievement of accounting conservatism. This study included the type of descriptive study verifying causality. The population in this study were Real Estate and Property Companies listed on the Indonesia Stock Exchange (IDX) in 2012-2017 with a sample of 17 companies selected using the purposive sampling method. The types of data collected and used in this study are secondary data with methods of collecting data through documentation and literature studies. The data analysis method used is simple linear regression analysis that has met the testing of classical assumptions. The results of the study indicate that the independent variable, namely good corporate governance. The results of multiple regression analysis indicate that the coefficient of determination of R Square = 67%, which means that all independent variables can explain the variation of the dependent variable, accounting conservatism is 67%.